Hermite Hadamard Type Inequalities Involving (k-p) Fractional Operator with (α, h − m) − p convexity (European Journal of Pure and Applied Mathematics, 2023)
We establish various fractional convex inequalities of the Hermite-Hadamard type which generalize the previously obtained results in the literature. Various types of such inequalities are obtained and given as corollaries. The main motivation of the paper is to generalize the recently published results in terms of the (α, h − m) − p convexity with k-p Riemann Liouville fractional operator. The application of H¨olders inequality is given in tandem with the k-p fractional operator of the convex type.
Keywords: Hermite-Hadamard-inequality; convex-function; Holder's inequality; Fractional Calculus